If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42k + -56 = -24 Reorder the terms: -56 + 42k = -24 Solving -56 + 42k = -24 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 42k = -24 + 56 Combine like terms: -56 + 56 = 0 0 + 42k = -24 + 56 42k = -24 + 56 Combine like terms: -24 + 56 = 32 42k = 32 Divide each side by '42'. k = 0.7619047619 Simplifying k = 0.7619047619
| 5/3+a=4/15 | | 6k-6=5k-2 | | X=6.8-.2y | | 5x-180=0 | | -(X+2)=3X-4 | | 6x+36=3x+81 | | 19x-2(x+10)=12 | | N+12=12+7 | | 3x-4/3+2x-8/4=5x+8/2 | | 3(2x+1)=34 | | 4/9x1/9 | | 1x-33=2+12 | | 5x+3(x+2)=19 | | 4x+10=10+4x | | 3z+2=6z-4z | | 4t^2-8t/(18-9t) | | 4+1/7+1/2 | | 18-n=9+3 | | -3.5x=12.25 | | 21-6=11 | | 7c=-42 | | 2+3x=7+3x | | 6x+9x-23=115-8x | | 8x+35=47 | | -4(3t-5)+8t=7t-5 | | 8/h=288 | | 10+17c+13c= | | -x-4=-13 | | b-24=16 | | 2/1/3+1/1/4 | | 19x+6y=71.90 | | x=4x-8/(x-4)(x+1) |